Muri di silenzio nella scatola nera della storia tedesca: tre opere documentarie di Andres Veiel sulla violenza (2001-2011) (Altre Modernità, 2021)
The subject of the wall, also in a symbolic sense, is a main topic in the worksof the German playwright and film director Andres Veiel. Focussing on three films anda play realised between 2001 and 2011 (Der Kick, Black Box BRD and Wer wenn nicht wir),the essay illustrates how Veiel’s works intend to unmask and contribute to tear down walls of silence and fear in the German individual and collective memory. Moreover, the article points out how Veiel, while concentrating on the hidden structures behindterrorism and violence, intentionally chooses to use minimalist, sober andunspectacular aesthetics which take inspiration from the epic and documentary theatre.
Keywords: Berlin Wall; Terrorism; Myth; German Cinema; Documentary Theatre; Epic Theatre